Estimating external costs of transportation in regional areas using available statistical data: the case of the region of Campania - Gallo, Mariano (TeMA - Journal of Land Use, Mobility and Environment, 2010)
In this paper simplified methods for estimating the external costs due to transportation in regional areas are proposed. The methods are based on data available by national and regional statistical sources and do not need specific surveys; they allow obtaining approximate estimates useful for a preliminary evaluation of transportation plans, policies and projects. Using the proposed methods the external costs of transportation in the region of Campania are estimated. First results show the relevance of external costs and the applicability of proposed methodologies for an Italian region; the same methodologies can be applied to regions of other European countries where the data are available.